2019
DOI: 10.1109/access.2019.2950066
|View full text |Cite
|
Sign up to set email alerts
|

Overall Population Generalities, Sex Differences, and Individual Differences in Sleep Electroencephalography Functional Connectivity

Abstract: Sleep is indispensable for humans to maintain normal life activities. Sex and individual differences in sleep patterns and quality of sleep cannot be ignored. Nevertheless, the overall population generalities and sex-or individual-differences in cerebral cortical functional connectivity (FC) during sleep have not been well described. Here, we evaluated the characteristic patterns of FC based on whole-night sleep electroencephalography (EEG) recordings. An improved weighted phase lag index (WPLI) algorithm was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 56 publications
(70 reference statements)
1
11
1
Order By: Relevance
“…WPLI can reflect the cortical oscillation relation between different sites in the same brain region or between different brain regions (Imperatori et al, 2020). An improved WPLI calculation method was used in this research (Liao et al, 2019), and its definition is as follows:…”
Section: Fc Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…WPLI can reflect the cortical oscillation relation between different sites in the same brain region or between different brain regions (Imperatori et al, 2020). An improved WPLI calculation method was used in this research (Liao et al, 2019), and its definition is as follows:…”
Section: Fc Analysismentioning
confidence: 99%
“…Previous studies have tried to explore different inter-regional features to exhibit differences in FC distribution, such as left-right asymmetry and anterior-posterior anisotropy (Liao et al, 2019;Pan et al, 2021;Zhou et al, 2020). It has been reported that the FC of the limbic system in the hemisphere of patients with depression is reduced (Cao et al, 2012), whereas Irwin et al found that the FC between the hemispheres of the amygdala was enhanced (Irwin et al, 2004).…”
Section: Inter-regional Fc Differencementioning
confidence: 99%
See 1 more Smart Citation
“…Developed from TE, the dSPTE has better noise robustness and can correctly identify the EC, and its calculation procedure contains phase information extraction, symbolic process, and true delay search. For phase information extraction, a combined Morlet wavelet was used to obtain the instantaneous phase ( Liao et al, 2019 ). The definition of a single Morlet complex wavelet is:…”
Section: Methodsmentioning
confidence: 99%
“…The research found that the fluctuation in delta frequency is higher in females than in males. In this experiment, 10-20 instruments were used for EEG recordings [11,17]. According to Ravan et al [12], frequent use of the 10-20 system can cause brain related disorders and therefore such experiments should be avoided.…”
Section: Literature Reviewmentioning
confidence: 99%